Discretionary food advertising on television in 2017: a descriptive study - Lisa G. Smithers; Xinyue Wang; Dandara Haag; Benjamin Agnew; John Lynch; Matthew Sorell (Elsevier, 2019)
Abstract Objective: To describe advertising of discretionary foods on television at times when children watch television. Methods: We randomly sampled 84 days (one of each weekday for every month of the year) for 2017, viewed all food advertisements and categorised them according to type (healthy, discretionary or other). The frequency of advertisements per hour was calculated for times when most children watch television (peak viewing time PVT1) and when C‐rated programs can be broadcast (PVT2). Results: The rate of advertising of discretionary foods during PVT1 was 1.5/hour (95%CI 1.4-1.5), and during PVT2 was 1.7/hour (1.6-1.8). Conclusions: Children continue to be exposed to food advertising. Implications for public health: Voluntary food and grocery industry codes have not prevented children from being exposed to discretionary food advertising on television. From June 2019, all food and beverage advertising is subject to either food industry or advertising industry codes. The data presented here will form the baseline for future evaluation of whether the new arrangements reduce children's exposure to food advertising.